Economic analysis of pumped hydro storage under Korean governmental expansion plan for renewable energy - Youngjun Ko; Gilyoung Choi; Siyoung Lee; Sungsoo Kim (Energy Reports, 2020)
A government plan was announced to expand the share of renewable energy to 20 percent by 2030 in Korea and to construct additional pumped hydro storage (PHS) to prepare for the uncertainty of renewable generation. However, due to the distortion of the Korean electricity market, pumped storage power plants are operating in the red, which may cause controversy over the economic feasibility of additional construction. In this study, we intend to analyze the exact economic value of the PHS in Korea under the plan for supplying electricity in 2030. To this end, an annual economic dispatch algorithm was developed using linear programming model and various scenarios were analyzed, including securing reserve power to cope with the variability of renewable energy. As a result of the analysis, we can confirm the economic feasibility of PHS prepare for expansion of renewable energy if PHS are correctly compensated according to the value contributing to the stable operation of the grid in the electricity market.
Keywords: 330; Economic analysis; Linear programming; Pumped hydro storage; Renewable energy